2020
DOI: 10.1002/jcp.29874
|View full text |Cite
|
Sign up to set email alerts
|

Gene interaction network approach to elucidate the multidrug resistance mechanisms in the pathogenic bacterial strain Proteus mirabilis

Abstract: Proteus mirabilis is one among the most frequently identified pathogen in patients with the urinary tract infection. The multidrug resistance exhibited by P. mirabilis renders the treatment ineffective, and new progressive strategies are needed to overcome the antibiotic resistance (AR). We have analyzed the evolutionary relationship of 29 P. mirabilis strains available in the National Center for Biotechnology Information-Genome database. The antimicrobial resistance genes of P. mirabilis along with the enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In Latin America, there are medical, social and ecological circumstances that favor a dynamic epidemiology of HCAI and CAI produced by Gram-negative bacteria, which are a public health problem, and their distribution varies among service units in a hospital, with the patient casuistry, sites of infection, antimicrobial administration protocols, types of infections, control practices and local resistance (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…In Latin America, there are medical, social and ecological circumstances that favor a dynamic epidemiology of HCAI and CAI produced by Gram-negative bacteria, which are a public health problem, and their distribution varies among service units in a hospital, with the patient casuistry, sites of infection, antimicrobial administration protocols, types of infections, control practices and local resistance (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics have been used indiscriminately for decades, resulting in the growth of multidrug resistance. Antibiotic resistance concerns global health regulatory bodies, and researchers are working around the globe to solve the problem [20]. In addition to the effects, increasing the constant need for antibiotics has resulted in the growth of antibiotic bacterial resistance over time.…”
Section: Bacterial Resistance Against Antibioticsmentioning
confidence: 99%
“…Recent studies have demonstrated the potential antibacterial activity of the novel SUL–DUR (βL–βLI) inhibitor combination, which is currently under Phase‐III clinical trials and may be helpful in treating infections caused by A. baumannii 9,11 . Our research group has worked extensively to understand the protein–ligand interactions and complex AMR mechanisms of pathogenic bacteria through genomic analyses, 12–15 in silico structural biology, 16–20 and the systems biology approach 21–24 . The present study aimed to decipher the efficacy of the SUL–DUR combination against clinical Indian isolates of A. baumannii .…”
Section: Introductionmentioning
confidence: 99%
“…9,11 Our research group has worked extensively to understand the protein-ligand interactions and complex AMR mechanisms of pathogenic bacteria through genomic analyses, [12][13][14][15] in silico structural biology, [16][17][18][19][20] and the systems biology approach. [21][22][23][24] The present study aimed to decipher the efficacy of the SUL-DUR combination against clinical Indian isolates of A. baumannii. This was achieved by characterising the intermolecular binding profiles of PBP3-SUL and β-lactamases-DUR complexes through in silico and in vitro analyses.…”
Section: Introductionmentioning
confidence: 99%